The Complex Interactions Between Obesity, Metabolism and the Brain - Uranga, Romina María; Keller, Jeffrey Neil (Frontiers in Neuroscience, 2019)
Obesity is increasing at unprecedented levels globally, and the overall impact of obesity on the various organ systems of the body is only beginning to be fully appreciated. Because of the myriad of direct and indirect effects of obesity causing dysfunction of multiple tissues and organs, it is likely that there will be heterogeneity in the presentation of obesity effects in any given population, and its analysis is far from linear. The focus of this review is to provide a comprehensive view of metabolic disturbances present in obesity, their direct and indirect effects on the different organ systems of the body, and to discuss the interaction of these effects in the context of aging and brain disease.